PENGARUH PROFESIONALISME GURU TERHADAP SEMANGAT KERJA GURU DI SMA PGRI 2 KOTA JAMBI - Benar Sembiring, Endah Lestari, (Universitas Batanghari Jambi, 2018)
This study aims to determine the description of respondents and the influence of professionalism of teachers to the spirit of teacher work in SMA PGRI 2 Kota Jambi. Based on the data analysis on the results of research that there is a significant influence between the professionalism of teachers to the spirit of teacher work in SMA PGRI 2 Kota Jambi. With result of model summary R = 0,203 and R Square = 0,241. Because α (Sig) <0.05, then regression can be used to predict teacher professionalism at 95% confidence level. In coefficient B constant value = 66,932, states that if teacher professionalism variable is ignored, then teacher's performance = 66,932. Meanwhile, the value of the variable for professionalism (X) is - 0.287, stating that if the level of professionalism of the teacher as involved, then the teacher's performance increases around - 0.287. Keyword : Teacher Professionalism, Teacher Performance